Performance appraisal employee performance decision-making system in determining salary increases using FSA methods - Febri Ainun Jariyah; Windu Gata; , Jordy Lasmana Putra; Frieyadie Frieyadie; Hafifah Bella Novitasari (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Employee performance appraisal is one of the important components of the company in the decision-making process of increasing employee salaries, salaries are wages paid to employees who work for the company, and all employees who work for the company are entitled to receive salaries in accordance with company regulations. The issue of salary acquisition is important because it has a significant impact on work ethic. This research is based on the decision-making process of employee salary increases based on length of service, position, latest education, absenteeism, and work assessment including KK, HK, SK, TJ, KS IK, KD, KP, KJ, KT, DK. The FSA concept can be applied to assist in checking or evaluating performance to determine the percentage increase in employee salary each year. The results of filling out the PA form will result in an increase in employee salary outputs of 0%, 5%, 10%, 15% and 20%. Automata are used to recognize and capture patterns when designing and manufacturing using FSA models.